Relationship between LDH Levels with COVID-19 Degree of Severity - Tambunan, Adrian Nurrachman; Ganie, Ratna Akbari; Tarigan, Amira Permatasari (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2023)
Background: LDH has proved to be a significant predictor for prognosis and follow-up in COVID-19 patients. Several studies report elevated LDH in hospitalized COVID-19 patients to be associated with a higher risk of death. Increased LDH levels can result from any tissue damage due to SARS-CoV-2 infection. The study aims to describe the relationship between LDH levels with COVID-19 19 degree of severity. Methods: This study is a cross-sectional study of 55 patients who confirmed positive by RT-PCR SARS-CoV-2 at H. Adam Malik General Hospital Medan (November 2021 – Maret 2022). Examination of the LDH level was carried out by the Chemiluminescent Immunoassays method (Abbott Architect). COVID-19 degree of severity was assessed based on the diagnostic criteria for COVID-19 cases in Indonesia. Results: Among the 55 COVID-19 patients in this study, the average age found was 45.73, with men 54.5%. Moderate, severe, and critical patients were found in 63.6%; 29.1%; and 7.3% respectively. The mean LDH level at admission was 278 U/L, higher in the severe (333.19 U/L) and critical (465.75 U/L) groups compared to the moderate (231.31 U/L) groups. Increased LDH ≥ 256 U/L proved to be related to COVID-19 degree of severity upon hospital admission (CI 95%; p = 0.001). Conclusions: LDH levels that increased ≥ 256 U/L were significantly related to COVID-19 degree of severity during hospital admission.